Challenges of the Organization of Educational Process in Ukraine during the COVID-19 Pandemic - KOVTUN, Iryna; TERESHCHENKO , Tetiana (University Scientific Notes, 2020)
The publication is devoted to the analysis of the challenges of the organization of educational process faced by the Ukrainian educational institutions during the COVID-19 pandemic. The complexity and ambiguity of the process of making managerial decisions in the field of education in the conditions of quarantine and the organization of distance learning have been emphasized. The relevant 3D model of management decision-making and the nature of management decisions made by our country's educational institutions as a response to the challenges of the COVID-19 pandemic are described. It has been systematized the peculiarities of psychological, communicative, financial, regulatory and organizational challenges, which should become new opportunities for educational institutions to improve their work and achieve the main goal of the activity, i.e. the provision of high-quality educational services. The expediency of using different services and platforms in the educational process at its different stages is analyzed. The list of competencies that are especially important in the conditions of using distance learning technologies, including the ability to experiment, to act at high speed, is substantiated; provide different processes in different roles, simultaneously with many participants and from different access points; use modern information technologies, computer systems, etc. The most important problems of communication between the participants of the educational process in the conditions of quarantine restrictions have been identified. The current legislation of Ukraine regulating distance learning has been systematized; the content and peculiarities of conducting distance learning and distance learning technologies that can be used on full-time and part-time forms of education have been clarified. Emphasis is also placed on the need to solve the problem of proper financial and logistical support of distance learning for all participants in the educational process. The main advantages and disadvantages of the organization of the educational process using remote technologies are determined. The main accents of distance learning organization are identified, which require detailed study and further implementation in Ukraine.
Keywords: education; educational institutions; educational process; distance learning; challenges; opportunities; quarantine; COVID-19 pandemic